Se construire dans le dialogue philosophique à l’adolescence, entre autonomie et vulnérabilité. - Agathe Delanoë (Éducation et Socialisation)
While the practices of philosophy for children are aimed at young people aged 4 to 17, it seems interesting to consider the adolescent experience as a determining factor in the experience of philosophical dialogue, as distinct from the child's experience. This exploratory qualitative research focuses on the practice of philosophical dialogue with adolescents, paying particular attention to the challenge of empowerment that characterizes this period. To empirically investigate this question, data were collected on three sites with different institutional contexts, two educational establishments with 14-15-years-olds and one care setting with 15-23-years-olds. Interviews and dialogues were recorded, and observation was carried out on these three sites. Data analyses combined conceptualizing category analysis and quantitative description. The results highlight three forms of adolescent vulnerability revealed in the dialogues and identify a dialectic liable to lead young people towards greater autonomy. Taking these vulnerabilities into account sheds light on adolescents' experience of the activity and calls for further reflection on the educational acts that can meet these vulnerabilities.